Tourniquet use for knee replacement surgery - Ahmed, Imran (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To determine the benefits and safety of tourniquets used in knee replacement surgery.